2019
DOI: 10.1111/psyp.13464
|View full text |Cite
|
Sign up to set email alerts
|

Brain flexibility associated with need for cognition contributes to creative achievement

Abstract: Advances in graph‐theoretic models of networks have made it possible to investigate the topological properties of the human brain across time and space. Brain flexibility is defined as the frequency with which brain regions switch between different functional modules over time and has been shown to correlate with higher‐order cognitive functions. Need for cognition (NFC) refers to a personality trait to engage in and enjoy effortful cognitive endeavors and usually has a positive effect on diverse cognitive act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 97 publications
(178 reference statements)
2
20
0
1
Order By: Relevance
“…Recent academic work supports the supposition that Need for Cognition indirectly indexes cognitive abilities, which indirectly influence decision‐making processes. For example, He et al (2019) observed that brain networks associated with Need for Cognition were also involved with higher‐order cognitive functions (i.e., executive control, salience detection, spontaneous thought, and motivation function). Collectively, this evidence indicates that the supposition that Need for Cognition indexes rational thought and in turn, belief in conspiracies is grossly oversimplified.…”
Section: Discussionmentioning
confidence: 99%
“…Recent academic work supports the supposition that Need for Cognition indirectly indexes cognitive abilities, which indirectly influence decision‐making processes. For example, He et al (2019) observed that brain networks associated with Need for Cognition were also involved with higher‐order cognitive functions (i.e., executive control, salience detection, spontaneous thought, and motivation function). Collectively, this evidence indicates that the supposition that Need for Cognition indexes rational thought and in turn, belief in conspiracies is grossly oversimplified.…”
Section: Discussionmentioning
confidence: 99%
“…After preprocessing, the brain network flexibility of each subject was calculated following some previous publications (21)(22)(23)(24)(25)29), which was summarized as follows (and also see Figure 1):…”
Section: Flexibility Of Dynamic Brain Networkmentioning
confidence: 99%
“…One of these novel features, for example, is the brain network flexibility which is defined by all brain regions' average rate of switching between different modules in the framework of dynamic network model (19,20). Such flexibility of dynamic brain network has been suggested to be an important fundamental feature of brain function (21), and has been reported to be associated with learning (20), cognition (22,23), emotion (24), as well as multiple mental diseases such as the major depressive disorder (25) and schizophrenia (26). Importantly, in a most recent study, a lower flexibility of EEG source-space brain network was found to be related with a higher psychological resilience in healthy adults, while no significant relationships were found between the psychological resilience and conventional static brain network metrics (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These more flexible areas were also characterized by relatively weak (but more variable) connection strengths, which was suggested to "enable the system to function within many difficult-to-reach states, reflecting a capacity to adapt to novel situations." Notably, flexibility in these areas has also been found to correlate with intelligence-related phenomena such as "need for cognition" and creative achievement (He et al, 2019). These flexible areas appear to constitute a combination of hubs from default mode networks involved in creative and imaginative cognition (Hassabis & Maguire, 2009), 'modeling' of self and other (Davey & Harrison, 2018;Saxe et al, 2006), frontoparietal control/attention networks (Huang et al, 2020), as well as salience-determining networks for high-level action selection (Rueter et al, 2018;Toschi et al, 2018).…”
Section: Characterizing Flexibility In Dynamic Networkmentioning
confidence: 99%